Detroit and the property tax : strategies to improve equity and enhance revenue - Sands, Gary; Skidmore, Mark (Policy focus series (Lincoln Institute of Land Policy), 2015)
This report outlines the problems underlying the erosion of Detroit's property taxbase--a factor that contributed to the city's bankruptcy in 2013. It offers recommendationsfor reform at the local and state level, as well as insight and analysis to help policymakers across the country protect their communities from economic decline.